2017
DOI: 10.1016/j.vaccine.2017.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A haemagglutinin specific IgG responses in children and adults after seasonal trivalent live attenuated influenza vaccination

Abstract: Influenza is a major respiratory pathogen and vaccination is the main method of prophylaxis. In 2012, the trivalent live attenuated influenza vaccine (LAIV3) was licensed in Europe for use in children. Vaccine-induced antibodies directed against the main viral surface glycoprotein, haemagglutinin (HA), play an important role in virus neutralization through different mechanism. The objective of this study was to dissect the HA specific antibody responses induced after LAIV3 immunization to the influenza A virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 165 publications
3
15
0
Order By: Relevance
“…Several European studies showed other results, and therefore, the EU continued to recommend use of LAIV in children . We have previously shown that LAIV immunization did not boost H1N1 HI titres in adults or children . Although children had significantly higher H1N1 HI titres than adults prior to and up to 56 days after vaccination, probably due to previous infection or the pandemic vaccination during the 2009 mass vaccination campaign.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Several European studies showed other results, and therefore, the EU continued to recommend use of LAIV in children . We have previously shown that LAIV immunization did not boost H1N1 HI titres in adults or children . Although children had significantly higher H1N1 HI titres than adults prior to and up to 56 days after vaccination, probably due to previous infection or the pandemic vaccination during the 2009 mass vaccination campaign.…”
Section: Discussionmentioning
confidence: 87%
“…Micro‐neutralization antibodies prevent infection and therefore are a direct measure of protection, although HA stalk‐specific antibodies may also confer protection through neutralization or by ADCC through Fc–FcγR interactions . We have previously reported a slight trend of an increase in group 1 HA stalk‐specific IgG in children after LAIV, but not in adults . Stalk‐specific neutralizing antibodies also showed a slight boost after the first dose in children, suggesting that LAIV could be used as a priming vaccine for inducing broadly cross‐reactive stalk responses.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations